2021
DOI: 10.1021/acs.inorgchem.1c01858
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Neptunium(V) in Alkali-Metal Hydroxides

Abstract: The preparation of two new neptunium hydroxide compounds synthesized in concentrated potassium and rubidium hydroxide is reported. The phases K 4 [(NpO 2 ) 2 (OH) 6 ]•4H 2 O and Rb 4 [(NpO 2 ) 4 (OH) 8 ]•2H 2 O were prepared and their chemical structures determined using single-crystal X-ray diffraction. Raman spectra of the compounds are also presented. The newly synthesized phases are structurally related to Np 2 O 5 and Na[NpO 2 (OH) 2 ]. The potassium-containing phase reported here consists of infinite cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…The Raman spectrum of Li 2 NpO 4 is very similar to that of Li 2 UO 4 but slightly red-shifted, as is commonly observed when moving across the actinide series. 7,46 Initial analysis suggested that the Raman spectrum of Li 2 NpO 4 is dominated by the symmetric stretching of the neptunyl cation at 693 cm −1 , displaying a typical ∼20 cm −1 red-shift compared to the uranium counterpart Li 2 UO 4 at 711 cm −1 . The Raman band associated with the symmetric -yl vibration is accompanied by a second band at 672 cm −1 in the case of Li 2 NpO 4 and 676 cm −1 in the case of Li 2 UO 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Raman spectrum of Li 2 NpO 4 is very similar to that of Li 2 UO 4 but slightly red-shifted, as is commonly observed when moving across the actinide series. 7,46 Initial analysis suggested that the Raman spectrum of Li 2 NpO 4 is dominated by the symmetric stretching of the neptunyl cation at 693 cm −1 , displaying a typical ∼20 cm −1 red-shift compared to the uranium counterpart Li 2 UO 4 at 711 cm −1 . The Raman band associated with the symmetric -yl vibration is accompanied by a second band at 672 cm −1 in the case of Li 2 NpO 4 and 676 cm −1 in the case of Li 2 UO 4 .…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, we have reported on the isolation of crystalline α-Na 2 NpO 4 from aqueous NaOH solutions under mild hydrothermal conditions and on the exploration of the synthetic phase space of Np in other alkali metal hydroxides under similar conditions, demonstrating a rich structural chemistry and complex redox behavior of neptunium in these hydroxide systems. These concentrated alkali hydroxide solutions are similar to those encountered in the legacy high-level waste tanks at the Hanford and Savannah River sites in the United States where large quantities of alkali metal hydroxides were added to neutralize the acidic process wastes resulting in a chemically complex environment encompassing high salt concentrations, low water activities, heat, and radiation fields . The best basis inventory values estimate there to be several hundred kilograms of Np in the waste tanks and identify Np as a long-term driver of dose risk .…”
Section: Introductionmentioning
confidence: 89%
“…18,19 In this work, we chose to prepare neptunyl and plutonyl acetate species through the oxidation of Np(IV) or Pu(IV) by ozonolysis in glacial acetic acid as seen in Figure 2; the isostructural uranium compound was prepared in the same manner using oxygen instead of ozone as the oxidant. Direct ozonolysis of acetic acid solutions containing the transuranic ions of interest proved to be an effective route to accessing the diacetate salts ] where M = Na, K, Rb, Cs and An = Np, Pu), [22][23][24][25] when mineral acid solutions are treated with alkali metal hydroxides to precipitate An(V) and An(VI). These actinyl materials carry the alkali metal ions through the reaction sequence, resulting in the formation of NaAnO 2 (CH 3 COO) 3 phases.…”
Section: Pu)mentioning
confidence: 99%
“…Actinide solution and solid-state structural chemistry continues to garner significant attention. This interest is motivated by fundamental needs such as understanding the role of the f-electrons in the behavior of heavy elements as well as challenges (and opportunities) in areas ranging from nuclear waste management to medicine. As an example, actinide structural chemistry has proved foundational to both our understanding of actinide behavior in the environment , and/or the development of actinide-based radiopharmaceuticals, both warranting insight into the conditions that drive the formation and stabilization of actinide structural units whether in solution or the solid state.…”
Section: Introductionmentioning
confidence: 99%